A tellurium iodide perovskite structure enabling eleven-electron transfer in zinc ion batteries - Shixun Wang; Zhiquan Wei; Hu Hong; Xun Guo; Yiqiao Wang; Ze Chen; Dechao Zhang; Xiaoyu Zhang; Xuyong Yang; Chunyi Zhi (Nature Communications)
Abstract The growing potential of low-dimensional metal-halide perovskites as conversion-type cathode materials is limited by electrochemically inert B-site cations, diminishing the battery capacity and energy density. Here, we design a benzyltriethylammonium tellurium iodide perovskite, (BzTEA)2TeI6, as the cathode material, enabling X- and B-site elements with highly reversible chalcogen- and halogen-related redox reactions, respectively. The engineered perovskite can confine active elements, alleviate the shuttle effect and promote the transfer of Cl- on its surface. This allows for the utilization of inert high-valent tellurium cations, eventually realizing a special eleven-electron transfer mode (Te6+/Te4+/Te2-, I+/I0/I-, and Cl0/Cl-) in suitable electrolytes. The Zn||(BzTEA)2TeI6 battery exhibited a high capacity of up to 473 mAh g-1 Te/I and a large energy density of 577 Wh kg-1 Te/I at 0.5 A g-1, with capacity retention up to 82% after 500 cycles at 3 A g-1. The work sheds light on the design of high-energy batteries utilizing chalcogen-halide perovskite cathodes.